2019
DOI: 10.3390/antibiotics8040201
|View full text |Cite
|
Sign up to set email alerts
|

Combating Antimicrobial Resistance in Singapore: A Qualitative Study Exploring the Policy Context, Challenges, Facilitators, and Proposed Strategies

Abstract: Antimicrobial resistance (AMR) is a global public health threat that warrants urgent attention. However, the multifaceted nature of AMR often complicates the development and implementation of comprehensive policies. In this study, we describe the policy context and explore experts' perspectives on the challenges, facilitators, and strategies for combating AMR in Singapore. We conducted semi-structured interviews with 21 participants. Interviews were transcribed verbatim and were analyzed thematically, adopting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The increased level of engagement was also observed in the animal health sector, as is evident in the “IAMResponsible” campaign for the animal and agricultural sector, specifically targeting veterinarians, farmers, students, and the general public. This finding is similar across other ASEAN countries and could likely be attributed to the increased awareness and advocacy at the global level through international initiations, such as the WHO’s World Antimicrobial Awareness Week in November annually [ 17 , 27 ]. However, some respondents noted that the level of attention on the issue tends to wane after these campaign activities.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The increased level of engagement was also observed in the animal health sector, as is evident in the “IAMResponsible” campaign for the animal and agricultural sector, specifically targeting veterinarians, farmers, students, and the general public. This finding is similar across other ASEAN countries and could likely be attributed to the increased awareness and advocacy at the global level through international initiations, such as the WHO’s World Antimicrobial Awareness Week in November annually [ 17 , 27 ]. However, some respondents noted that the level of attention on the issue tends to wane after these campaign activities.…”
Section: Discussionsupporting
confidence: 58%
“…Insufficient infrastructure to support a national surveillance system has also been reported by other countries [ 29 ]. For example, Thailand highlighted a lack of national policy decisions for the development of a comprehensive surveillance system; Singapore mentioned that, although surveillance in the human health sector was well established, it was mainly limited to the public sector, and it was also lacking in the animal health and environment sectors [ 27 , 31 ]. The antimicrobial usage (AMU) surveillance in the Philippines was also reported to be insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Their qualitative ndings suggested that promoting awareness among policymakers and stakeholders is of critical importance to reduce the burden of AMR. (Singh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous case study in Singapore has shown that the progress of AMR initiatives can be compromised regardless of resource allocation and that combating AMR is also complex in high-resource settings such as Singapore. Their findings suggest that promoting awareness among policy-makers and stakeholders is of critical importance to reduce the burden of AMR [ 15 ].…”
Section: Introductionmentioning
confidence: 99%